2010
DOI: 10.1111/j.1365-2702.2009.03186.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among nutritional self‐efficacy, health locus of control and nutritional status in older Taiwanese adults

Abstract: Nurses can help older persons identify factors that relate to their nutritional status and plan effective interventions to maintain healthy nutrition behaviours with the following risk characteristics: (1) lower level of education, (2) more chronic diseases and (3) external control orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 46 publications
2
39
1
Order By: Relevance
“…A lower level of education has been found to be a risk factor in other studies 5,50. According to Feldblum et al,50 education ≤ 12 years could predict undernutrition.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A lower level of education has been found to be a risk factor in other studies 5,50. According to Feldblum et al,50 education ≤ 12 years could predict undernutrition.…”
Section: Discussionmentioning
confidence: 86%
“…They found that 28% were at risk of undernutrition, ie, a higher prevalence than in our study. However, it can be expected that older people visiting a clinic were a more homogeneous group with respect to personal health, and thereby had a higher risk of undernutrition, because disease is known to have a negative effect on nutritional status 5–7. In our study, the sample is assumed to mirror the heterogeneity of home-dwelling older people, ie, from healthy younger older people to very old people who are expected to be suffering from illness and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These associations may explain the common association of older age with poor nutritional status (Nyk€ anen et al 2013). Older adults in Taiwan have been shown to have poor nutritional knowledge, insufficient dietary intake and inadequate nutritional status (Department of Health 2004, Chen et al 2010, Chen & Shao 2012. Furthermore, older adults' dietary issues have been related to seven of the ten leading causes of their death in Taiwan (Ministry of Health & Welfare 2013) and a systematic review found that nutrition was commonly associated with mortality of older hospitalized adults and nursing home residents in western countries (Thomas et al 2013).…”
Section: Introductionmentioning
confidence: 99%